Pengukuran waktu standar pembuatan produk sampan komposit sandwich untuk menentukan biaya poduksi - I.M. Suartika; A.D. Catur; M. Mirmanto (Dinamika Teknik Mesin, 2021)
In the efforts to develop the boat of composite sandwichto overcome the scarcity of wood as a boat material, thedetermination of production costs becomes veryimportant to be studied. The purpose of this study is toconduct a study related to the amount and time requiredin the completion of product units with the stop watchtime study method. The results of the time study wereused to determine the cost or wages of labor in theproduction of the boat composite sandwiches. So that allcomponents of these costs will later determine thefeasibility of production of the boat composite sandwichproducts. Based on the results of the measurement ofwork time study known standard time production of theboat composite sandwich with two people labor and shiftwork 8 hours / day is 34 hours (equivalent to 5 days) andproduction capability 5 units / month. The results ofresearch related to production process costs are knownfixed costs (FC )= Rp. 1,288,655 and variable costs /units (c) = Rp. 2,664,333. By conducting break-evenpoint analysis obtained minimum production units permonth that can be produced by setting the selling price( ) of the product based on profit margin 5%, 10%,15%, 20%, 25%, i.e consecutively; 10 units/month, 5units/month, 4 units/month, 3 units/month, 2 units/month.